RPE65: Role in the visual cycle, human retinal disease, and gene therapy - Cai, Xue (2009)
RPE65 is an isomerohydrolase expressed in retinal pigment epithelium. It is critical for the regeneration of the visual pigment necessary for both rod and cone-mediated vision. Mutations in human RPE65 cause Leber’s congenital amaurosis and other forms of autosomal recessive retinitis pigmentosa which are associated with early-onset blindness. Several RPE65 animal models including two different mouse models and a naturally occurring canine model have been thoroughly characterized to determine the mechanisms that underlie RPE65 associated retinal dystrophies. More recently, substantial effort has gone into designing gene therapies for these diseases. Based on several encouraging reports from animal models, at least three clinical trials are currently underway for the treatment of LCA using modified AAV vectors carrying the RPE65 cDNA and have reported positive preliminary results.